Kesesakan lalu lintas di bandar Segamat, Johor - Sulaiman, Shamsul Ariff (2016)
Traffic congestion is an issue which disturb the movement and the smoothness of the citizens in dealing with their daily routine. The district of Segamat has experienced rapid development, especially in urban areas. However, the development has lead to slow traffic flow in the city of Segamat by the influx of vehicles entering the city hall. Therefore, the goal of this study is to provide recommendations on appropriate measures to overcome the causes of congestion. The sample of study involved Segamat City’s road users and government departments which involved with the planning and execution of the transport system and road network in the area in Segamat district. They are the Local Public Works Department of Segamat, the Segamat District Council, the Department of Traffic Police Segamat and the Segamat District Land Office. Data were obtained through questionnaire filled out by the respondents and interviews with senior officers of the departments involved. The data were analyzed quantitatively and qualitatively. The results showed that all respondents agreed with the road or traffic congestion occurred in City of Segamat. Traffic congestion occurs mainly during festivals or celebrations and the peak hours of morning and evening of the daily routine. There are six causes of congestion namely the conditions and structural design of roads, the improvement of living standards of population, the attitude of drivers, the increase in urban population, the closing roads and the public transport services that are less than perfect. The results of the data analysis provides benefits to local communities and road users that went through City of Segamat to the route of East and West Coast. There are four proposals and measures for improvement identified in accordance with the pattern and development of City of Segamat that is the alternative route or the Segamat Bypass, restricting the entry of heavy vehicles into the urban space, the use of directional signage and implementation of one-way streets in the city of Segamat. The conclusion is that the traffic congestion that occurred needs the view of all parties either from the citizens and the governments department. It will guide thus significant for all parties involved in the planning and execution of the transport system and road network especially in the area of District of Segamat.